Wickerhamomyces anomalous: A Rare Cause of Fungemia Causing Febrile Neutropenia in Acute Lymphoblastic Leukemia - Vibha Mehta; Aroop Mohanty; Suneeta Meena; J. S. Rahul; Nath Uttam Kumar; Debranjani Chattopadhyay; Anamika Bakliwal; Ranjana Choudhary; Pratima Gupta (Case Reports in Infectious Diseases)
Candida bloodstream infection is the major cause of increased morbidity and mortality (20–49%) in hospitalized patients in both paediatric and adult age groups. Due to the increase in the number of immunocompromised patients, other important species such as Trichosporon asahii and Debaryomyces hansenii are emerging. One such organism, Wickerhamomyces anomalous, previously known as Pichia anomala (teleomorph stages of several Candida species), is increasingly being reported as a cause of fungemia in neonatal intensive care units and is now increasingly being reported in a lot of immunosuppressive conditions such as interstitial lung disease, endocarditis, enteritis, corticosteroids, and chemotherapy uptake. Though this yeast is ubiquitous in nature, systemic infections from isolated cases and sporadic outbreaks with high mortality have been reported in ICUs, which emphasize the importance to consider this fungus within the diagnostic possibilities. Here, we report a case of catheter-related bloodstream infection (CRBSI) caused by W. anomalus in a leukemic immunosuppressed patient who was successfully treated by early detection and treatment of this emerging fungus.